2005
DOI: 10.1111/j.1744-6198.2005.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Relapse: A Concept Analysis

Abstract: The concept of relapse has had many and varied applications in research literature. Great confusion exists in the application of the term to scientific measurement within the various studies. Therefore, an in-depth analysis of the generic term relapse was undertaken through the evolutionary approach offered by Rodgers and Knafl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…28 Recently, there has been increased interest in the differentiation of abstinence terminology in tobacco abstinence research. 25,[29][30][31][32] In these studies, a "lapse" accounts for an instance of smoking, while "relapse" generally refers to a return to baseline smoking, or a resumption of smoking at least five cigarettes for three consecutive days. In this context, a lapse is considered a temporary event, while a relapse indicates a more Figure 1.…”
Section: Measurement Of Abstinence Relapse and Shsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Recently, there has been increased interest in the differentiation of abstinence terminology in tobacco abstinence research. 25,[29][30][31][32] In these studies, a "lapse" accounts for an instance of smoking, while "relapse" generally refers to a return to baseline smoking, or a resumption of smoking at least five cigarettes for three consecutive days. In this context, a lapse is considered a temporary event, while a relapse indicates a more Figure 1.…”
Section: Measurement Of Abstinence Relapse and Shsmentioning
confidence: 99%
“…Historically, relapse described a phenomenon or a medical condition that had returned, such as cancer or a fever. 25 Relapse in the postpartum smoking literature is typically defined as any return to smoking, "even a puff." 26,27 Relapse has also been synonymous with the term "lapse" in tobacco abstinence literature.…”
Section: Measurement Of Abstinence Relapse and Shsmentioning
confidence: 99%
“…Constructing knowledge through academic literature is not a new concept (Dudas, 2012). Concept analysis is a specific research technique that is found in the literature to be an effective manner that describes concepts that are unclear and ambiguous (All & Huycke, 2007;Axley, 2008;Baldwin, 2008;Dudas, 2012;Purdy, 2004;Simonelli, 2005). Concept analysis has its roots in constructivist theory, but more importantly, it seems to build a theoretical bridge of understanding for Indigenous concepts.…”
Section: Indigenous Concept Analysismentioning
confidence: 99%
“…38 Likewise, a mother's level of confidence to remain tobacco free significantly affects relapse rates. 39,40 Without support to remain abstinent after birth, a mother's level of confidence wanes, and a relapse is predictable.…”
mentioning
confidence: 98%